Comparison of the Bacterial Gut Microbiome of North American Triatoma spp. With and Without Trypanosoma cruzi - Mann, Allison E.; Mitchell, Elizabeth A.; Zhang, Yan; Curtis-Robles, Rachel; Thapa, Santosh; Hamer, Sarah A.; Allen, Michael S. (Frontiers in Microbiology, 2020)
Chagas disease, caused by the hemoflagellate protist Trypanosoma cruzi, affects nearly 6 million people worldwide, mainly in Latin America. Hematophagous triatomine insects (‘kissing bugs’) are the primary vectors of T. cruzi throughout the Americas and feed on a variety of animals, including humans. Control of triatomines is central to the control of T. cruzi infection. Recent advances in mitigation of other insect-borne diseases via the manipulation of insect-associated bacteria as a way to halt or slow disease transmission has opened questions to the applicability of these methods to Chagas disease vectors. Few studies have examined the hindgut microbiome of triatomines found in North America. In the current study, two species of triatomines were collected across Texas, USA, screened for the presence of T. cruzi, and analyzed for the bacterial composition of their hindguts using a 16S rRNA gene-fragment metabarcoding approach. We compared diversity of microbial community profiles across 74 triatomine insects to address the hypothesis that the richness and abundance of bacterial groups differ by T. cruzi infection and strain type, blood meal engorgement status, insect species, sex, and collection location. The gut microbial community of individual triatomines was characterized by low intraindividual taxonomic diversity and high interindividual variation that was weakly predicted by triatomine species, and was not predicted by triatomine sex, collection location, T. cruzi infection status, or blood meal score. However, we did find bacterial groups enriched in T. cruzi-positive individuals, including Enterobacterales, and Petrimonas. Additionally, we detected Salmonella enterica subspecies diarizonae in three triatomine individuals; this species is commonly associated with reptiles and domesticated animals and is a pathogen of humans. These data suggest that Triatoma spp. in Texas have variable patterns of colonized and transient bacteria, and may aid in development of novel means to interfere with transmission of the Chagas disease parasite T. cruzi. Deeper understanding of the effects of parasite infection on diverse insect vector microbiomes may highlight disease transmission risk and facilitate discovery of possible intervention strategies for biological control of this emerging vector-borne disease of global health significance.